Characterization of the yeast population from tradiotional corn and rye bread doughs - Almeida, M. J. (1996)
Yeasts were isolated from a variety of home-made bread doughs and identified. A pure culture of Saccharomyces cerevisiae was found in 18%of the doughs. The same species predominated in 80% of the doughs examined whereas Issatchenkia orientalis, Pichia membranaefaciens and Torulaspora delbrueckii were present in about 40% of the samples. About one quarter of the isolates displayed killer activity, strains of P. anomala showing the broadest spectra. Two isolates of S. cerevisiae and three of T. delbrueckii gave biomass values in sucrose medium similar to or higher than those obtained with commercial compressed baker´s yeast strains.